2015
DOI: 10.1371/journal.pone.0134458
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Up-Regulates Galectin-3 in Mammary Tumor Progression and Metastasis

Abstract: The tumor microenvironment encompasses several stressful conditions for cancer cells such as hypoxia, oxidative stress and pH alterations. Galectin-3, a well-studied member of the beta-galactoside-binding animal family of lectins has been implicated in multiple steps of metastasis as cell-cell and cell-ECM adhesion, promotion of angiogenesis, cell proliferation and resistance to apoptosis. However, both its aberrantly up- and down-regulated expression was observed in several types of cancer. Thus, the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 60 publications
(81 reference statements)
0
30
0
1
Order By: Relevance
“…In Her-2 negative breast cancer cells, galectin-3 in concert with Annexin-A 2 modulates the epidermal growth factor receptor pathway which promotes cancer development [146]. In breast tumour development, hypoxia significantly increases production of galectin-3 which seems to be responsible for an aggressive phenotype while in concert with senescent cell-derived growth factors, galectin-3 induces colorectal cancer cells growth [147,148]. Hoffmann et al (2002) have observed that in the eye, Advanced Glycation End Products (AGEs) not only that increase in newly formed blood vessels but also promote proliferation of Müller cells, retinal pigment epithelial cells, and choroidal endothelial cells [149].…”
Section: K Galectinsmentioning
confidence: 99%
“…In Her-2 negative breast cancer cells, galectin-3 in concert with Annexin-A 2 modulates the epidermal growth factor receptor pathway which promotes cancer development [146]. In breast tumour development, hypoxia significantly increases production of galectin-3 which seems to be responsible for an aggressive phenotype while in concert with senescent cell-derived growth factors, galectin-3 induces colorectal cancer cells growth [147,148]. Hoffmann et al (2002) have observed that in the eye, Advanced Glycation End Products (AGEs) not only that increase in newly formed blood vessels but also promote proliferation of Müller cells, retinal pigment epithelial cells, and choroidal endothelial cells [149].…”
Section: K Galectinsmentioning
confidence: 99%
“…Cat-D has spacious substrate specificity at acidic pH which leads to degradation of proteins and composition of mature activated peptides in endosomes (5) . Galectin-3 (Gal-3) is a carbohydrate-binding protein which mediates cell-cell and cell-extracellular matrix (ECM) interactions (6) . Gal-3 is not only an intracellular protein that can be found both in the cytoplasm and nucleus but it is also an extracellular protein that can be present on the cell surface or the extracellular matrix (7) .…”
Section: ıNtroductıonmentioning
confidence: 99%
“…It seems that the translocation of Galectin-3 from the cytoplasm to the nucleus of melanoma cells results in a more aggressive phenotype (57). Interestingly, tumour hypoxia upregulates the expression of Galectin-3 and also leads to changes in its subcellular localization (58). Under hypoxic conditions, the expression of Galectin-3 shifts from a nuclear location to cytoplasmic and membranous locations, suggesting that this shift favours resistance to apoptosis and malignancy of mammary tumour cells (58).…”
Section: Protumourigenic Role Of Galectin3mentioning
confidence: 99%
“…Interestingly, tumour hypoxia upregulates the expression of Galectin-3 and also leads to changes in its subcellular localization (58). Under hypoxic conditions, the expression of Galectin-3 shifts from a nuclear location to cytoplasmic and membranous locations, suggesting that this shift favours resistance to apoptosis and malignancy of mammary tumour cells (58). Circulating Galectin-3 is also increased in the bloodstream of cancer patients.…”
Section: Protumourigenic Role Of Galectin3mentioning
confidence: 99%